2010
DOI: 10.1073/pnas.1002746107
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Forkhead signaling by the retinal determination factor DACH1

Abstract: The Drosophila Dachshund (Dac) gene, cloned as a dominant inhibitor of the hyperactive growth factor mutant ellipse, encodes a key component of the retinal determination gene network that governs cell fate. Herein, cyclic amplification and selection of targets identified a DACH1 DNA-binding sequence that resembles the FOX (Forkhead box-containing protein) binding site. Genome-wide in silico promoter analysis of DACH1 binding sites identified gene clusters populating cellular pathways associated with the cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 31 publications
6
71
0
Order By: Relevance
“…Mutations in the Pax6 locus cause impaired insulin secretion, early-onset diabetes mellitus, and aniridia (16,32,33). A recent genome-wide in silico promoter analysis identified Glucagon and Igf2 as potential targets of mammalian Dach1 (34). In addition, a diet-induced β-cell-dysfunction analysis in mice identified that the altered expression of several genes, including Dach1, is correlated significantly with data from genome-wide association studies for type 2 diabetes in humans (35).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the Pax6 locus cause impaired insulin secretion, early-onset diabetes mellitus, and aniridia (16,32,33). A recent genome-wide in silico promoter analysis identified Glucagon and Igf2 as potential targets of mammalian Dach1 (34). In addition, a diet-induced β-cell-dysfunction analysis in mice identified that the altered expression of several genes, including Dach1, is correlated significantly with data from genome-wide association studies for type 2 diabetes in humans (35).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies used for IP and WB were: anti-T7; (Bethyl Laboratories, Montgomery, TX), anti-FLAG (M2 clone; Sigma), anti-FOXM1 (C20; Santa Cruz), and anti-DACH1 (Abcam; Cambridge, MA). ChIP analysis was performed following a protocol described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…A DACH1-specific DNA binding sequence was recently identified (14). To characterize the biological significance of DACH1 DNA binding further, we cloned a 13-bp DACH1 binding sequence, designated as DRE, into pGL3 luciferase reporter vectors pGL3-SV40 and pGL3-basic (Promega).…”
Section: Dach1 Encodes a Heterologous Transcriptional Repressor-mentioning
confidence: 99%
See 2 more Smart Citations